Operando visualisation of lithium plating by ultrasound imaging of battery cells - David Wasylowski; Heinrich Ditler; Morian Sonnet; Tim Falkenstein; Luca Leogrande; Emanuel Ronge; Alexander Blömeke; Andreas Würsig; Florian Ringbeck; Dirk Uwe Sauer (Nature Communications)
Abstract While developing battery cells, the achievement of fast-charging capability is heavily dependent on avoiding metallic plating on the anode surface (i.e., lithium plating in lithium-ion cells). However, this objective hinges on the effectiveness of plating detection. Currently, measurement techniques are either inadequate in providing spatial, temporal, or causal information, incur high costs when employing, e.g., neutron imaging, or are lengthy due to destructive post-mortem examinations that additionally lack operando data. In this work, we demonstrate an ultrasound imaging method for operando visualization of the interior of a multi-layer pouch battery cell. Here we show that this method can non-invasively visualize the formation and stripping of lithium plating during cycling. Extensive reference electrode studies and ex-situ analysis verify the effectiveness of our method for plating detection. Ultimately, this work enables researchers and industry to significantly accelerate the development of new cell technologies and their optimized utilization.